What determines residual income? - CHENG, Qiang (Institutional Knowledge at Singapore Management University, 2005)
This paper investigates the determinants of residual income scaled by book value of equity, i.e., abnormal return on equity (ROE), by analyzing the impact of value-creation (economic rents) and value-recording (conservative accounting) processes on abnormal ROE. I rely on economic theories to characterize economic rents and develop an empirical measure—the conservative accounting factor—to capture the effect of conservative accounting. As expected, industry abnormal ROE increases with industry concentration, industry-level barriers to entry, and industry conservative accounting factors. Also as expected, the difference between firm and industry abnormal ROE increases with market share, firm size, firm-level barriers to entry, and firm conservative accounting factors. Integrating these determinants into the residual income valuation model significantly increases its explanatory power for the variation in the market-to-book ratio.